TCP‐polite rate control based on cooperative measurement. Issue 9 (18th November 2013) - Wang, Wen‐Yong; Huang, Li‐Sheng; Li, Chang‐Chun; Wang, Xin
Abstract: Based on the cooperative measurement of new congestion metric instead of drop ratio and round‐trip time, a new cooperative transmission control mechanism, called TCP‐polite rate control (TPRC), is proposed. In this scheme, the congestion metric of network is obtained with cooperative measurement and feeds back to rate‐based pacing mechanism, thus keeping the transmission rate at the lower bound of available bandwidth. Simulation results show that TPRC scheme outperforms TCP and TCP‐friendly rate control protocol in terms of fast‐start, efficiency, and fairness. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A new cooperative transmission control mechanism, called TCP‐polite rate control (TPRC), is proposed. In this scheme, the congestion metric of network is obtained with cooperative measurement and feeds back to rate‐based pacing mechanism, thus keeping the transmission rate at the lower bound of available bandwidth.